2019
DOI: 10.26605/medvet-v13n2-3072
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de prevalência de parasitos zoonóticos em amostras de fezes de cães em vias públicas de quatro bairros do município de Pelotas-RS

Abstract: As parasitoses zoonóticas transmitidas por animais de companhia possuem um caráter de agressão nos próprios animais e em seres humanos em alguns casos e ainda tem pouca divulgação junto à comunidade. O objetivo deste trabalho foi estimar a prevalência de parasitos zoonóticos em quatro bairros do município de Pelotas-RS. Foram realizadas coletas de amostras de fezes de caninos em vias públicas referente aos bairros Bom Jesus, Simões Lopes, Navegantes e Barro Duro, processadas pela técnica de Willis-Mollay (1921… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
1
1
Order By: Relevance
“…The gender Trichuris vulpis was identified in 3.33% of the samples. With results superior to those of the present study, Savilla et al (2011), Barros et al (2018), Chagas et al (2019) and Antunes et al (2020) diagnosed the parasite in 7.8%, 20.70%, 20.8% and 10.88% of the samples evaluated, in West Virginea, the United States, and in Brazil, specifically, in Pelotas, Rio Grande do South, Valença and Rio de Janeiro, respectively.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…The gender Trichuris vulpis was identified in 3.33% of the samples. With results superior to those of the present study, Savilla et al (2011), Barros et al (2018), Chagas et al (2019) and Antunes et al (2020) diagnosed the parasite in 7.8%, 20.70%, 20.8% and 10.88% of the samples evaluated, in West Virginea, the United States, and in Brazil, specifically, in Pelotas, Rio Grande do South, Valença and Rio de Janeiro, respectively.…”
Section: Resultscontrasting
confidence: 73%
“…Of the total samples evaluated, it was found that the genus Ancylostoma caninum was the most abundant, totaling 24 (80%); the other information is contained in Table 1. In this context, corroborating this study, Chagas et al (2019) evaluated the feces of dogs belonging to different districts and municipalities, at the time the presence of ancylostoma was diagnosed in 63.81% of the animals evaluated. Barros et al (2018) conducted a study in Rio de Janeiro on public roads and found the presence of Ancylostoma spp.…”
Section: Resultssupporting
confidence: 65%
“…Among the zoonotic parasitoses associated with dogs in tropical, subtropical and temperate regions are toxocariasis, cystic echinococcosis (CE) and visceral leishmaniasis, (Otranto et al 2017). Some parasites registered in South America, such as Echinococcus granulosus, T. canis and Ancylostoma caninum (Chagas et al 2019;Ritossa et al 2021), can cause diverse zoonotic diseases like CE and the larva migrans visceral and cutaneous syndromes (Amundson Romich 2008). Other parasites, like Trichuris vulpis, are distributed throughout the world but rarely transmitted to humans.…”
Section: Introductionmentioning
confidence: 99%